Integrated Marketing Communication (IMC) Strategy of @kueliam to Increase Sales during Ramadan 2025 - Veronica Winata; Teguh Poeradisastra (Institut Komunikasi dan Bisnis LSPR, 2025)
This study aims to examine a partial and adaptive implementation of integrated marketing communication (IMC) applied by a micro and small enterprise (MSE) during a seasonal campaign, and to identify empirical indications of its contribution to sales performance. A qualitative case study approach is used to explore communication practices carried out across various channels, both online and offline. Data is collected through participant observation and documentation, and analysed using the Miles & Huberman model. The findings reveal that although all elements of the marketing communication mix were taken into consideration, Kue Liam, as an MSE, was only able to implement two main channels: direct selling and online & social media marketing. These two channels proved effective in reaching consumers, fostering engagement, and significantly driving sales during the Ramadan period. This study offers practical insights into the application of IMC by MSEs in the context of seasonal campaigns and serves as a strategic reference for similar businesses.